DOCUMENTING DEATH: MATERNAL MORTALITY AND THE ETHICS OF CARE IN TANZANIA (ADRIENNE E. STRONG 2020) - Oktavia, Luluk; Sukarno, Megawati (UI Scholars Hub, 2025)
In recent decades, global efforts to reduce maternal mortality have become a primary focus in health development agendas. However, challenges in providing quality healthcare remain complex, especially in resource-limited countries. Adrienne E. Strong’s book, Documenting Death: Maternal Mortality and the Ethics of Care in Tanzania, offers an ethnographic perspective on the relationship between bureaucratic structures, resource constraints, and healthcare practices in Tanzania. This review examines Strong’s key concepts, such as good enough care, documented care, and fierce care, which highlight the ethical dilemmas faced by healthcare workers in delivering care under administrative pressures and limited facilities. The critique of the ethnographic approach in this book also addresses its limitations in offering broader systemic solutions and its relevance to other national contexts, such as Indonesia. This paper seeks to connect Strong’s analysis with global maternal health challenges, emphasizing the importance of understanding the interaction between global policies and local practices to improve maternal and infant healthcare quality.